HeroZ : empower yourself, your coworkers, your company - Byham, William C.; Cox, Jeff (New York : Harmony Books, 1994)
In HeroZ, you'll actually have fun learning how to survive and even thrive in today's work world. Step-by-step techniques - proven by thousands of companies around the globe - show you how to make meaningful decisions, measure your progress, and work efficiently in teams. By the time you finish reading HeroZ, you'll feel that you control your job, not that your job controls you.
Keywords: Psychology, Industrial; Interpersonal relations; Labor productivity